A Fungal Diterpene Synthase Is Responsible for Sterol Biosynthesis for Growth - Liu, Yanjie (Front Microbiol, 2020)
A conserved open reading frame, dps, is described in Pestalotiopsis microspora, sharing a remarkable similarity with fungal diterpene synthases whose function is less studied. Loss-of-function approach manifested that dps was necessary for the growth and the development of the fungus. A deletion strain, dpsΔ, showed a fundamental retardation in growth, which could deliberately be restored by the addition of exogenous sterols to the media. Gas chromatography–mass spectrometry analysis confirmed the loss of the ability to produce certain sterols. Thus, the tolerance and the resistance of dpsΔ to several stress conditions were impaired. Secondary metabolites, such as the polyketide derivative dibenzodioxocinones, were significantly diminished. At the molecular level, the deletion of dps even affected the expression of genes in the mevalonate pathway. This report adds knowledge about fungal diterpene synthases in Pestalitiopsis microspora.